Answer:
a) (-3, 0) and (7, 0)
b) If x = 7 then (7 - 7) = 0
If x = -3 then (-3 + 3) = 0
c) f(x) = x² - 4x - 21
y-intercept (0, -21)
Explanation:
a)
x-intercepts are when f(x) = 0
Therefore, if f(x) = (x - 7)(x + 3) then (x - 7)(x + 3) = 0
⇒ x - 7 = 0
⇒ x = 7
and
⇒ x + 3 = 0
⇒ x = -3
So x-intercepts are (-3, 0) and (7, 0)
b) If x = 7 then (7 - 7) = 0
If x = -3 then (-3 + 3) = 0
c) Expand f(x) = (x - 7)(x + 3)
⇒ f(x) = x² + 3x - 7x - 21
⇒ f(x) = x² - 4x - 21
The y-intercept is when x = 0 ⇒ (0, -21)